Influence of Reaction Temperature on Optical Property of Mn-Doped ZnS Nanoparticles - Van, Bui Hong; Ben, Pham Van; Nhat, Hoang Nam (Communications in Physics, 2013)
The reaction temperature has essential effect on quality of the product synthesized by hydrothermal method. We report here the variation of the optical characteristics of Mn-doped ZnS nanocrystallites prepared by mean of the stated method from Zn(CH$_{3}$COO)$_{2}$.2H$_{2}$O, Mn(CH$_{3}$COO)$_{2}$.4H$_{2}$O and Na$_{2}$S$_{2}$O$_{3}$.5H$_{2}$O as the precursors. The reaction temperature was set to vary from 120\r{}C to 240\r{}C at a constant reaction time of 15 hours. The XRD patterns showed that, for the reaction temperature range from 120 to 160\r{}C, the obtained products possessed a cubic $T_d^2 - F\overline 4 3m$ and a wurtzite $C_{6v}^4 - P6_3 mc$structure, in which the cubic phase was dominant. At the temperature range from 180 to 240\r{}C, the structures exhibited a cubic phase with the lattice constant increased from 5.41 to 5.43 Å. The photoluminescence spectra showed that with the increase of reaction temperature from 120 to 240\r{}C the intensity of a blue band around 425 - 500 nm (attributed to both Zn, S vacancies) gradually decreased while the intensity of a yellow-orange band at 585 nm (attributed to the $^{4}$T$_{1}(^{4}$G) - $^{6}$A$_{1}(^{6}$S) transition of Mn$^{2 + }$ ions) was enhanced and reached maximum at 220\r{}C. The excitation spectra of the 585 nm band recorded at 160\r{}C showed a band at 335 nm which should be assigned to the near band-edge absorption. With increasing temperature to 200-240\r{}C the new bands appeared at 390, 430, 467, 494 nm. The intensity of these bands increased with temperature and achieved the maxima at 220\r{}C. They should be attributed to the absorption transitions of electrons from ground state $^{6}$A$_{1}(^{6}$S) to excited states$^{ 4}$E($^{4}$D); $^{4}$T$_{2}(^{4}$D); $^{4}$A$_{1}(^{4}$G) - $^{4}$E($^{4}$G); $^{4}$T$_{2}(^{4}$G) of Mn$^{2 + }$(3d$^{5})$ ions, respectively. The bands at 467, 494 nm only exposed clearly in the absorption spectra at 220\r{}C and 240\r{}C.